Sintered body with excellent impact resistance

The sintered body with zirconia and stabilizers promotes plastic deformation to enhance impact resistance, addressing the brittle failure of ceramics under dynamic loads.

JP2025015776AActive Publication Date: 2025-01-30TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024201770
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-12-10
Filing Date
2024-11-19
Publication Date
2025-01-30
Estimated Expiration
2040-12-08

AI Technical Summary

Technical Problem

Ceramics, despite their high mechanical characteristics and chemical stability, are prone to brittle failure under dynamic impacts, leading to cracks and destruction.

Method used

A sintered body containing zirconia with specific stabilizer contents and a plastic deformation area that absorbs and disperses impact energy, preventing brittle failure by promoting plastic deformation.

Benefits of technology

Enhances impact resistance by prioritizing the occurrence of plastic deformation over brittle failure, improving the sintered body's ability to withstand impacts beyond its destruction resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015776000001_ABST
    Figure 2025015776000001_ABST
Patent Text Reader

Abstract

To provide at least one of a sintered body with improved impact resistance achieved by generating impact absorption through plastic deformation prior to the occurrence of brittle fracture in response to an impact that exceeds the fracture resistance of the sintered body, and a manufacturing method for the sintered body.SOLUTION: A sintered body that comprises zirconia containing a stabilizer and that has an area in which an impact mark is formed when an impact force is applied is provided.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sintered body having excellent impact resistance, and in particular to a sintered body having excellent impact resistance and made mainly of zirconia. [Background technology]

[0002] Compared to metallic materials, ceramics have high mechanical properties and chemical stability, but are also brittle materials. Therefore, when a dynamic impact is applied at room temperature, such as when dropped, sintered bodies such as zirconia ceramics are prone to fracture due to the initiation and propagation of cracks, i.e., brittle fracture. In order to prevent such brittle fracture, improvements in fracture toughness are being investigated.

[0003] For example, Patent Document 1 discloses a method for forming a zirconia alloy containing 4 mol% yttria with SrAl 12 O 19 It has been reported that the fracture toughness can be improved by dispersing cubic Sr in zirconia. x It has been reported that dispersion of NbO3 improves fracture toughness and drop resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-037746 A [Patent Document 2] Special Publication No. 2019-501855 Summary of the Invention [Problem to be solved by the invention]

[0005] The improvement in impact resistance in Patent Documents 1 and 2 was the result of improved fracture resistance obtained by improving fracture toughness. In both sintered bodies, when subjected to an impact exceeding the fracture resistance, brittle fracture such as the generation of cracks first occurs, and then the fracture progresses to cause fracture. Thus, the fracture mechanism in both sintered bodies was caused only by brittle fracture.

[0006] In response to this, the present disclosure aims to provide at least one of a sintered body and a manufacturing method thereof, in which shock absorption through plastic deformation occurs prior to the occurrence of brittle fracture in response to an impact that exceeds the fracture resistance of the sintered body, thereby improving impact resistance. [Means for solving the problem]

[0007] The present inventors have investigated ways to improve the impact resistance of ceramics, and have found that the improvement in impact resistance can be achieved through a mechanism different from that of improved fracture toughness.

[0008] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] A sintered body comprising zirconia containing a stabilizer and having a region in which an impact mark is formed when an impact force is applied. [2] The sintered body according to the above [1], wherein the impact mark is a recess. [3] The sintered body according to the above [1] or [2], wherein the stabilizer content is 3 mol % or more and 10 mol % or less. [4] The sintered body according to any one of the above [1] to [3], wherein the stabilizer is two or more selected from the group consisting of yttria, calcia, magnesia and ceria. [5] The sintered body according to any one of the above [1] to [4], wherein the stabilizer is yttria and ceria. [6] The sintered body according to any one of [1] to [5] above, having an yttria content of less than 1.5 mol%. [7] The sintered body according to any one of [1] to [6] above, having a ceria content of 2 mol % or more and 7.5 mol % or less. [8] The sintered body according to any one of [1] to [7] above, which contains alumina. [9] The sintered body according to any one of [1] to [8] above, having a region in which the ratio of the powder X-ray diffraction peak intensity of the tetragonal (004) plane to the powder X-ray diffraction peak intensity of the tetragonal (220) plane is greater than 0 and less than or equal to 1.0.

[10] The sintered body according to any one of [1] to [9] above, having a region in which the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane is greater than 1.0 and less than 10 relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane when an impact force is applied.

[11] The sintered body according to any one of [1] to

[10] above, having a Vickers hardness of 12 GPa or less.

[12] A member comprising the sintered body according to any one of [1] to

[11] above. Effect of the Invention

[0009] The present disclosure makes it possible to provide at least one of a sintered body and a manufacturing method thereof, in which shock absorption through plastic deformation occurs prior to the occurrence of brittle fracture in response to an impact that exceeds the fracture resistance of the sintered body, thereby improving impact resistance. [Brief description of the drawings]

[0010] [Figure 1] Schematic diagram showing the state of a drop ball test using a DuPont type drop ball tester [Diagram 2] FIG. 13 is a schematic diagram showing an example of an impact core (formation of a recess) after a ball drop test. [Diagram 3] Schematic diagram showing an example of the impact core area of ​​a high-hardness sintered body after a ball drop test [Figure 4] Schematic diagram showing an example of the arrangement of measurement samples in a drop ball test [Diagram 5] Schematic diagram showing how to measure the depth of impact marks [Figure 6]Schematic diagram showing an example of the mode of destruction caused by a ball drop test: (a) state where destruction has occurred, (b) state where destruction has not occurred [Figure 7] Appearance of the sintered body of Example 1 after the drop test [Figure 8] Appearance of impact marks formed on the sintered body of Example 1 after a drop test (magnification: 20 times) [Figure 9] Appearance of the sintered body of Comparative Example 3 after drop test (magnification: 20 times) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the sintered body of the present disclosure will be described with reference to an example of an embodiment.

[0012] The sintered body of the present embodiment is a sintered body that contains zirconia containing a stabilizer and has a region in which an impact mark is formed when an impact force is applied.

[0013] The sintered body of the present embodiment contains zirconia containing a stabilizer, and is preferably a so-called zirconia sintered body having zirconia containing a stabilizer as a matrix (main phase). Since the sintered body of the present embodiment contains a stabilizer, it can also be considered as a partially stabilized zirconia sintered body.

[0014] The sintered body of this embodiment has a region where an impact mark is formed when an impact force is applied. One of the reasons why the impact resistance of the sintered body of this embodiment is improved, that is, the impact resistance is improved, is that the region where the impact mark is formed (hereinafter also referred to as the "plastic deformation region") exhibits the function of absorbing and dispersing the energy transmitted by the applied impact force. As a result, when an impact force is applied, at least plastic deformation occurs prior to the occurrence of brittle fracture, and as a result, the occurrence of brittle fracture is suppressed and the impact resistance is improved.

[0015] The sintered body of this embodiment may have a plastic deformation region in at least a portion of the sintered body (i.e., may be a sintered body having a plastic deformation region), but may be composed mainly of a plastic deformation region or may be a sintered body composed of a plastic deformation region.

[0016] The term "impact force" refers to a force that transmits energy to a sintered body, particularly a dynamic external force, preferably an external force that exceeds the fracture resistance of the sintered body, more preferably a dynamic external force that exceeds the fracture resistance of the sintered body, and further a dynamic external force that exerts elastic energy on the sintered body.

[0017] "When an impact force is applied" refers to a state in which energy is applied to at least a part of the sintered body, such as when the sintered body falls and comes into contact with the ground, or when a dropped object comes into contact with the sintered body, and energy is dynamically applied to the sintered body as a result of the sintered body coming into contact with an object.

[0018] The "impact mark" is a mark of impact force applied to the sintered body, preferably a mark formed on the sintered body by application of impact force. In other words, the impact mark is a mark of plastic deformation of the sintered body, that is, a mark of plastic deformation that occurs prior to destruction. Specific examples of the impact mark include a concave or concave portion, a concave portion, or a concave portion along the direction of application of the impact force in the impact core portion (described later).

[0019] In this embodiment, whether or not the sintered body has a plastic deformation region can be confirmed by applying an impact force (for example, a dynamic external force that advances the destruction of the sintered body) to the sintered body by any method. By applying an impact force to the sintered body and confirming the formation of an impact mark as a trace of plastic deformation such as a recess or uneven portion (particularly, a trace of deformation prior to destruction) on the sintered body after the impact force is applied, it can be confirmed that the sintered body has a plastic deformation region. In the sintered body of this embodiment, the impact mark is formed due to plastic deformation, but may include defects such as cracks that occur after (after the formation of the impact mark). On the other hand, if there are only defects such as cracks (i.e., only defects are confirmed without the formation of impact marks due to plastic deformation) or only deformation due to destruction such as Hertzian destruction (i.e., only deformation formed by the development of destruction such as cracks that occurred initially is confirmed; FIG. 9, dotted circle), it can be determined that there is no plastic deformation region.

[0020] A preferred method for confirming the presence of a plastic deformation region is a ball drop test (hereinafter simply referred to as the "ball drop test"), in which a DuPont ball drop tester conforming to JIS K 5600 5-3 is used to drop a 300 g weight from a height of 350 mm at room temperature.

[0021] FIG. 1 is a schematic diagram showing a ball drop test using a DuPont type ball drop tester. As shown in FIG. 1, in the ball drop test, a measurement sample (101) is attached with a protective tape (107) on the back side, placed on a cylindrical sample stage (106) of the ball drop tester, and fixed to the sample stage by attaching a fixing tape (105) to the side. The drop weight is composed of a weight (104) and a punch (102), and the punch (102) is placed on the surface of the measurement sample (101). The ball drop test can be performed by dropping the weight (104) from the punch from a height equivalent to the drop height (height corresponding to the double arrow in FIG. 1; 350 mm). The punch (102) has a cylindrical shape with a spherical (semi-spherical) tip. This allows the same impact force to be applied to the measurement sample as when a hard ball of the same size as the spherical surface is dropped from the drop height. By dropping the weight (104) along the guides (103a, 103b) of the DuPont type ball drop tester, a desired impact force can be applied to the measurement sample (101) via the hitting mold (102). If a hitting mold is not used, a hard ball with a mass of 300 g and the same diameter as the spherical part (hemispherical part) of the hitting mold may be dropped onto the measurement sample from a height equivalent to the drop height.

[0022] FIG. 2 is a schematic diagram showing the appearance of the sintered body of this embodiment after a ball drop test. As shown in FIG. 2, it can be confirmed that the sintered body of this embodiment has an impact mark formed in the region where the impact force of the falling weight (striking die) was applied by the ball drop test (hereinafter also referred to as the "impact core part"). The impact mark in FIG. 2 shows a state where a recess is formed near the impact core part, and it can be visually confirmed that there is a plastic deformation region. Although not shown, there may be defects such as cracks near the recess. In contrast, FIG. 3 is a schematic diagram showing the appearance of a conventional sintered body after a ball drop test. As shown in FIG. 3, the conventional sintered body does not show the formation of an impact mark at the impact core part, and only defects such as cracks are generated.

[0023] The presence or absence of a plastically deformed region may be confirmed by at least one of visual inspection and observation with an optical microscope, and more preferably by visual inspection. The magnification in observation with an optical microscope is, for example, 1 to 100 times, and preferably 10 to 30 times.

[0024] Although not shown in the figure, a conventional sintered body with high fracture toughness (for example, a fracture toughness value of 7 MPa m as measured by the SEPB method) 0.5 In the case of sintered bodies with a thickness exceeding 350 mm, the appearance does not change before and after the ball drop test, and the impact core cannot be confirmed. In this case, the ball drop test is performed by increasing the drop height until the impact core can be confirmed, and the presence or absence of a plastic deformation region can be confirmed by confirming the formation of impact marks such as the formation of recesses and the occurrence of defects in the confirmed impact core. However, in the sintered body of this embodiment, the presence or absence of a plastic deformation region can be confirmed by performing a ball drop test at a ball drop height of 350 mm.

[0025] In this embodiment, the ball drop test can be performed at room temperature (20 to 30° C.) using a DuPont type ball drop tester conforming to JIS K 5600 5-3. The conditions for the ball drop test include the following. Falling weight: (shape) A spherical hard ball with a diameter of 6.35 mm or a cylindrical punch with a spherical tip with a diameter of 6.35 mm (mass) 300g Drop height: 350mm Measurement sample: A sintered body with a plate shape of 40 mm length x 30 mm width x 2 mm thickness, both surfaces of which have a surface roughness of Ra≦0.02μm

[0026] To prevent the sample pieces from scattering, the measurement sample is placed on the sample stage of the ball drop tester by fixing one surface of the sample (40 mm long x 30 mm wide) with double-sided tape. After placement, fixation tape (protective tape) is applied vertically to the main surface that pairs with the surface on which the measurement sample is fixed, to fix the measurement sample in place (Fig. 4). The ball drop test can then be carried out on the fixed measurement sample.

[0027] The depth of the impact mark formed by the ball drop test may be, for example, the depth of the deepest part of the impact mark (204 in Fig. 2) relative to the thickness of the sintered compact (203 in Fig. 2) of the sintered compact, which may be more than 0 and not more than 3.5, or even more than 0.5 and not more than 3. Note that the depth (204) of the impact mark (concave) in Fig. 2 is shown with the depth emphasized.

[0028] In this embodiment, the depth of the impact mark can be measured using a general laser microscope (for example, VK-9500 / VK-9510, manufactured by Keyence Corporation). The observation magnification can be, for example, 10 to 50 times, or even 20 times, and the laser wavelength can be 408 nm.

[0029] FIG. 5 shows a schematic diagram of a method for measuring the depth of an impact mark. In the measurement, a line profile (503A) is made that passes through the center of the impact mark, and the length (L1) of the deepest part in the Z-axis direction is measured. Similarly, a similar line profile (503B) is made so as to be perpendicular to the line profile, and the length (L2) of the deepest part in the Z-axis direction is measured. The lengths of both the deepest parts obtained are averaged (=(L1+L2) / 2), and the obtained length is taken as the depth (504) of the impact mark. The measurement condition for measuring the length of the deepest part can be 0.5 μm / step, for example. Prior to the measurement, a standard sample (e.g., a Si substrate with a pattern engraved on it) attached to the device with a known pattern length is measured, and the analysis accuracy is adjusted.

[0030] Such analyses such as line profile and measurement of the deepest part in the Z-axis direction can be performed by image analysis using analysis software attached to the laser microscope (for example, software name: VK-H1A9VK ANALYZER Version 3.0.1.0).

[0031] The zirconia contained in the sintered body of this embodiment contains a stabilizer. The stabilizer may contain an element having a function of stabilizing zirconia, and is preferably two or more selected from the group consisting of yttria (Y2O3), calcia (CaO), magnesia (MgO) and ceria (CeO2), more preferably contains at least yttria, more preferably contains one or more selected from the group consisting of calcia, magnesia and ceria and yttria, and further preferably contains yttria and ceria.

[0032] The stabilizer content is the total ratio (mol%) of the stabilizer calculated as oxide to the total of zirconia and the stabilizer calculated as oxide. The stabilizer content may be an amount that partially stabilizes zirconia, and for example, the stabilizer content in a sintered body made of zirconia containing yttria and ceria (yttria and ceria stabilized zirconia sintered body) can be calculated as {(Y2O3+CeO2) / (Y2O3+CeO2+ZrO2)}×100 (mol%). The stabilizer content is preferably 3 mol% or more and 10 mol% or less, more preferably 4 mol% or more and 7.5 mol% or less, even more preferably 4.2 mol% or more and 6.2 mol% or less, even more preferably 4.5 mol% or more and 6.0 mol% or less, and even more preferably 4.6 mol% or more and 5.5 mol% or less.

[0033] When yttria is contained as a stabilizer, the yttria content is preferably less than 1.5 mol%, more preferably 1.3 mol% or less, and even more preferably 1.2 mol% or less. When ceria coexists with yttria, a sintered body is easily obtained by a simple method such as normal pressure sintering, so the yttria content is more than 0 mol%, preferably 0.5 mol% or more, more preferably 0.6 mol% or more, and particularly preferably 0.9 mol% or more, and even more preferably 1.0 mol% or more.

[0034] The sintered body of the present embodiment may satisfy the above-mentioned stabilizer content, but the ceria content in the case where the stabilizer contains ceria is arbitrary. The ceria content may be, for example, 2 mol% to 7.5 mol%, further 2.5 mol% to 6 mol%, or further 3 mol% to 5 mol%. In the case where the stabilizer contains calcia, the calcia content may be, for example, 2 mol% to 7.5 mol%, further 2.5 mol% to 6 mol%, and in the case where the stabilizer contains magnesia, the magnesia content may be, for example, 2 mol% to 7.5 mol%, further 2 mol% to 6 mol%.

[0035] The sintered body of this embodiment preferably contains ceria and yttria as stabilizers, and in this case, the ceria content is preferably 2 mol% or more, 3 mol% or more, or 3.5 mol% or more, and 6 mol% or less, 5.5 mol% or less, or 4.5 mol% or less, and the yttria content is preferably 0.1 mol% or more, 0.5 mol% or more, or 0.9 mol% or more, and less than 1.5 mol%, 1.3 mol% or less, or 1.15 mol% or less.

[0036] The content of each stabilizer is the ratio (mol%) of each stabilizer calculated as an oxide to the total of zirconia and the stabilizer calculated as an oxide. For example, the yttria content in yttria-stabilized zirconia is the ratio (mol%) of yttria to the total of zirconia and yttria, and can be calculated from {(Y2O3 / (Y2O3+ZrO2))×100(mol%). The ceria content in ceria-stabilized zirconia is the ratio (mol%) of ceria to the total of zirconia and ceria, and can be calculated from {(CeO2 / (CeO2+ZrO2))×100(mol%). The yttria content in yttria and ceria-stabilized zirconia sintered bodies can be calculated as {Y2O3 / (Y2O3+CeO2+ZrO2)}×100(mol%). In the present embodiment, ceria is preferably made of tetravalent cerium, and more preferably does not contain trivalent cerium.

[0037] Since impact marks due to plastic deformation tend to occur more easily, the ratio (molar ratio) of a stabilizing element other than yttrium to yttrium (Y) in the sintered body of this embodiment (hereinafter also referred to as the "S / Y ratio", and when the stabilizer other than yttrium is cerium (Ce) or the like, also referred to as the "Ce / Y ratio", etc.) is preferably 1.2 or more and 5.0 or less, more preferably 1.4 or more and 4.5 or less, even more preferably 1.5 or more and 2.3 or less, and even more preferably 1.6 or more and 2.0 or less.

[0038] The sintered body of this embodiment may contain alumina (Al2O3). This tends to improve mechanical properties, such as static strength. The sintered body of this embodiment may not contain alumina, so the alumina content is 0 mass% or more. When alumina is contained, the alumina content is more than 0 mass% and less than 30 mass%, preferably more than 0 mass% and 20 mass% or less, more preferably 0.005 mass% or more and 10 mass% or less. The alumina content may be 0 mass% or more, more than 0 mass%, 0.5 mass% or more, or 1 mass% or more, and 20 mass% or less, 17 mass% or less, 12 mass% or less, 10 mass% or less, or 8 mass% or less. The alumina content can be calculated as the mass ratio of aluminum calculated as Al2O3 to the total amount of zirconia, stabilizer calculated as oxide, and aluminum calculated as Al2O3. For example, when zirconia contains yttria and ceria as stabilizers, the alumina content can be calculated as {Al2O3 / (ZrO2+Y2O3+CeO2+Al2O3)}×100 (mass %).

[0039] Alumina (Al2O3) has a large effect on the mechanical properties of the sintered body, but has almost no effect on coloring zirconia. Therefore, in this embodiment, alumina, i.e., aluminum that does not form a complex oxide with a metal element, etc., is not included in the pigment.

[0040] The sintered body of the present embodiment preferably contains zirconia containing a stabilizer and is a so-called zirconia sintered body or a partially stabilized zirconia sintered body, which contains zirconia containing a stabilizer as a matrix (main phase). When zirconia containing a stabilizer is used as a matrix (main phase), the mass ratio of the zirconia containing a stabilizer in the sintered body (hereinafter also referred to as "zirconia content") is 70 mass% or more, preferably 80 mass% or more, and more preferably more than 90 mass%. When the sintered body has a zirconia content of 100 mass% or less and is composed only of zirconia containing a stabilizer, the mass ratio of zirconia is 100 mass%. The zirconia content can be calculated as the ratio of the total mass of zirconia and the stabilizer calculated as an oxide to the mass of the sintered body calculated as an oxide. For example, when the sintered body contains alumina and the remainder is zirconia containing yttria and ceria as stabilizers, the content of the zirconia containing the stabilizer can be calculated as {(ZrO2+Y2O3+CeO2) / (ZrO2+Y2O3+CeO2+Al2O3)}×100 (mass%).

[0041] The sintered body of this embodiment may contain inevitable impurities such as hafnia (HfO2), but preferably does not contain anything other than stabilizers, zirconia, alumina, and inevitable impurities. In this embodiment, values ​​that are affected by the composition, such as the content and density of each component, can be calculated by regarding hafnia (HfO2) as zirconia (ZrO2).

[0042] The sintered body of this embodiment preferably has a high density, and more preferably has a density equivalent to a relative density of 98% or more. In particular, the density tends to decrease as the alumina content increases. For example, when the alumina content is 0% by mass or more and 10% by mass or less, the lower limit of the measured density is 5.85 g / cm. 3 or more than 5.90g / cm 3 or more, with an upper limit of 6.20 g / cm 3 Below that, 6.10g / cm 3 Below 6.00g / cm 3When the alumina content is more than 10 mass% and not more than 20 mass%, the measured density is 5.30 g / cm 3 More than 5.85g / cm 3 When the alumina content is more than 20% by mass and less than 30% by mass, the measured density is 5.20 g / cm 3 More than 5.30g / cm 3 The reasons for this include that it is less than 100%.

[0043] In this embodiment, the measured density can be determined by Archimedes' method, and is a value determined as the mass determined by mass measurement relative to the volume determined by Archimedes' method.

[0044] The zirconia crystal phase of the sintered body of the present embodiment preferably contains at least tetragonal crystals, and may be composed of at least one of tetragonal crystals and cubic crystals and monoclinic crystals.

[0045] The sintered body of the present embodiment has a ratio of the powder X-ray diffraction peak intensity of the tetragonal (004) plane to the powder X-ray diffraction peak intensity of the tetragonal (220) plane (hereinafter referred to as "I (004) / (220) It is preferable that the crystal has a region where the (220) plane of the tetragonal crystal (hereinafter, referred to as "T") is greater than 0 and is not greater than 1.0 (hereinafter, referred to as "randomly oriented region"). It is more preferable that the crystal is made of a randomly oriented region. 220 ") and the tetragonal (004) plane (hereafter referred to as "T 004 " are crystal planes that are perpendicular to each other. (004) / (220) It is believed that the presence of the randomly oriented region is a sufficient condition for plastic deformation to occur when an impact force is applied. (004) / (220) is preferably 0.1 or more and 0.7 or less, and more preferably 0.2 or more and 0.6 or less.

[0046] When the sintered body of the present embodiment absorbs or disperses the energy caused by the application of an impact force, a change in the crystal orientation may occur in the plastic deformation region. For example, when an impact force is applied (after the application of an impact force), the crystal orientation of the plastic deformation region may become higher, and further, when an impact force is applied, the T 220 The intensity of the powder X-ray diffraction peaks of T 004 The powder X-ray diffraction peak intensity of the powder X-ray diffraction pattern is more than 1.0 and 10 or less (hereinafter, also referred to as "highly oriented region"). (004) / (220) is preferably 1.5 or more and 8.0 or less, and more preferably 3.0 or more and 5.0 or less.

[0047] In this embodiment, the powder X-ray diffraction pattern (X-ray diffraction pattern) of the sintered body can be measured by a general X-ray diffraction device for crystallinity analysis (for example, device name: X'pert PRO MPD, manufactured by Spectris).

[0048] The measurement conditions are as follows: Radiation source: CuKα radiation (λ=1.5405Å) Tube voltage: 45kV Tube current: 40mA High-speed detector: X'Celerator + Ni filter Micro optical system: Monocapillary, diameter 0.1 mm Measurement angle: 70~80° Goniometer: Radius 240mm

[0049] In the above measurement, T 004 The diffraction intensity of is the diffraction intensity (area intensity) of the XRD peak having a peak top at 2θ = 72.5 ± 1°, T 220 The diffraction intensities of the above are confirmed as the diffraction intensity (area intensity) of an XRD peak having a peak top at 2θ=74±1°, respectively.

[0050] The shape of the sintered body of the present embodiment may be at least one selected from the group consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron. Furthermore, any shape may be used to achieve a desired purpose, such as various applications.

[0051] The sintered body of this embodiment has a ball drop strength of 1 J or more, preferably 1.5 J or more. The ball drop strength is an index of impact resistance, and the higher the value, the higher the impact resistance. The ball drop strength of the sintered body can be, for example, 10 J or less, 5 J or less, or 4 J or less.

[0052] The ball drop strength in this embodiment is the energy imparted to a sintered body by a falling weight when the sintered body is broken when the falling weight is dropped from a predetermined ball drop height onto the sintered body. The ball drop strength can be calculated from the following formula, and is preferably a value when the sample thickness is 2 mm.

[0053] Fall strength (J) = falling weight mass (g) x falling height (mm) x gravitational acceleration (m / s 2 ) The acceleration due to gravity is 9.8m / s 2 can be used.

[0054] The ball drop strength can be measured in the same manner as in the above-mentioned ball drop test, except that the ball is dropped from any height as shown below. Drop height: 50~500mm

[0055] Breakage can be judged as occurring when the measurement sample is divided into two or more pieces (FIG. 6(a)). On the other hand, if a crack occurs that does not reach from one end to the other (FIG. 6(b)), it can be deemed that no breakage has occurred. If no breakage occurs in the ball drop test at a specific drop height, the ball drop test can be repeated by increasing the drop height in 50 mm increments up to 500 mm until breakage occurs, and visual observation can be performed in the same manner. In this embodiment, for measurement samples that do not break in the ball drop test at a drop height of 500 mm, the ball drop strength can be conveniently determined to be >5J (more than 5J).

[0056] The sintered body of the present embodiment preferably exhibits improved impact resistance due to plastic deformation, not improved impact resistance due to improved hardness.Since plastic deformation tends to occur easily, the Vickers hardness (Hv) of the sintered body of the present embodiment is preferably 12 GPa or less, more preferably 11 GPa or less, and even more preferably 10 GPa or less.

[0057] In this embodiment, the Vickers hardness can be measured by a method in accordance with JIS R1610: 2003. The following conditions can be exemplified as the conditions for measuring the Vickers hardness. Measurement sample: (sample thickness) 1.5±0.5mm (Measured surface roughness) Ra≦0.02μm Measurement load: 10kgf

[0058] The measurement can be performed using a general Vickers tester (e.g., MV-1, manufactured by Matsuzawa Co.) equipped with a square pyramid indenter made of diamond. The measurement is performed by statically pressing the indenter into the surface of the measurement sample, and visually measuring the diagonal length of the indentation mark formed on the surface of the measurement sample. Using the obtained diagonal length, the Vickers hardness can be calculated from the following formula. Hv=F / {d 2 / 2sin(α / 2)}

[0059] In the above formula, Hv is the Vickers hardness (GPa), F is the measurement load (10 kgf), d is the diagonal length of the indentation mark (mm), and α is the facing angle of the indenter (136°).

[0060] In this embodiment, the fracture toughness value can be exemplified as an index of the fracture resistance of the sintered body. The fracture toughness value is the fracture toughness value (MPa m 0.5) The fracture toughness value is measured using a columnar sintered body sample with a support distance of 30 mm, width of 4 mm and thickness of 3 mm, and the average value of 10 measurements may be regarded as the fracture toughness value of the sintered body of this embodiment. In addition, JIS R 1607 specifies two methods of fracture toughness measurement, the IF method and the SEPB method. Since the IF method is a simple measurement method, there is a large variation in the measured values ​​for each measurement. Therefore, the absolute values ​​of the fracture toughness value of this embodiment and the fracture toughness value measured by the IF method cannot be compared.

[0061] The color tone of the sintered body of this embodiment is arbitrary, but it is within the scope of CIE1976(L * a * b * ) Lightness in color space L * The lightness L is, for example, 80 or more, further 85 or more, and further 90 or more. * The upper limit is 100 or less.

[0062] Lightness L * The lightness L can be measured using a general spectrophotometer (e.g., CM-700d, manufactured by Konica Minolta) according to a method conforming to JIS Z8722. * The measurement conditions are as follows: It is preferable to perform the measurement using a black board as the background (so-called black back measurement). Light source: F2 light source Viewing angle: 10° Measurement method: SCI

[0063] A disk-shaped sintered body with a diameter of 20 mm and a thickness of 2.7 mm is used as a measurement sample, and the surface to be evaluated is mirror-polished (Ra≦0.02 μm) to evaluate the color tone. The effective area for color tone evaluation is 10 mm in diameter.

[0064] The sintered body of the present embodiment, particularly a sintered body not containing a pigment, has the above-mentioned lightness L * In this case, it is preferable that the saturation a * and b * For example, the saturation a of the sintered body of this embodiment tends to be small.* and b * are -6≦a * ≦-2 and 10≦b * ≦30.

[0065] The sintered body of the present embodiment can be applied to the applications of conventional sintered bodies, particularly zirconia sintered bodies such as structural materials, optical materials, and dental materials, but can also be used as a member that requires relatively high impact resistance, such as decorative items, covers for accessories such as watches and housings, and exterior components for portable electronic devices such as mobile phones.

[0066] Further preferred embodiments include the following. (1) A sintered body containing one or more stabilizers selected from the group consisting of calcia, magnesia, and ceria, yttria, and the balance being zirconia, in which the stabilizer content is 2 mol% or more and 7.5 mol% or less, and the yttria content is more than 0 mol% and less than 1.5 mol%, and which has a region in which the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane is more than 0 and is 1.0 or less relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane. (2) The sintered body according to the above (1), wherein the stabilizer is ceria. (3) The sintered body according to (1) or (2), wherein the total content of the stabilizer and the yttria is 4 mol % or more and 7.5 mol % or less. (4) The sintered body according to any one of (1) to (3) above, wherein the sintered body has a region in which the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane is greater than 0 and is not greater than 1.0. <Other embodiments> Another embodiment of the present disclosure is a sintered body having a region where an impact mark is formed when an impact force is applied.

[0067] Another embodiment of the present disclosure is a sintered body that is characterized in that an impact mark is formed when an impact force is applied thereto.

[0068] Another embodiment of the present disclosure is a sintered body, characterized in that a recess is formed by a ball drop test in which a 300 g weight is dropped from a height of 350 mm at room temperature using a DuPont ball drop tester conforming to JIS K 5600 5-3.

[0069] Another embodiment of the present disclosure is a sintered body having a region where the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane is greater than 0 and not greater than 1.0 relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane, and having a region where the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane is greater than 1.0 and not greater than 10 relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane after an impact force is applied.

[0070] In these embodiments, the sintered body is preferably a zirconia sintered body, more preferably a partially stabilized zirconia sintered body, even more preferably an yttria- and ceria-stabilized zirconia sintered body, and even more preferably an yttria- and ceria-stabilized zirconia sintered body having an yttria content of 1.0 mol% or more and less than 1.5 mol%.

[0071] The method for producing the sintered body of this embodiment will be described below.

[0072] The sintered body of this embodiment may be produced by any method as long as the sintered body satisfies the above requirements. An example of the method for producing the sintered body of this embodiment is a production method having a step of sintering a compact containing two or more stabilizer sources and zirconia.

[0073] The molded body to be subjected to the above step (hereinafter also referred to as "sintering step") is a molded body (compressed powder) containing two or more stabilizer sources and zirconia.

[0074] The stabilizer source may contain an element that becomes a stabilizer by sintering, and may be a compound containing one or more elements selected from the group consisting of yttria, calcia, magnesia, and ceria, or precursors thereof, yttrium (Y), calcium (Ca), magnesium (Mg), and cerium (Ce) (hereinafter, the stabilizer source when the stabilizer is yttria is also referred to as "yttria source" or the like). The stabilizer source is preferably a compound containing at least one of yttria and ceria, or precursors thereof, yttrium and cerium, and more preferably at least one of a compound containing yttrium and yttrium, and at least one of a compound containing ceria and cerium.

[0075] The yttria source may be at least one of yttria and its precursor yttrium compound, and may be one or more selected from the group consisting of yttrium chloride, yttria, and yttrium carbonate, with yttria being preferred.

[0076] The ceria source may be at least one of ceria and a cerium compound that serves as a precursor thereof, and may be one or more selected from the group consisting of cerium chloride, ceria, and cerium carbonate, with cerium chloride being preferred.

[0077] The calcia source may be at least one of calcia and a calcium compound which is a precursor thereof, and may be one or more selected from the group consisting of calcium chloride, calcia, calcium carbonate, and calcium hydrogen carbonate, with calcia being preferred.

[0078] The magnesia source may be at least one of magnesia and a magnesium compound that serves as a precursor thereof, and may include one or more selected from the group consisting of magnesium chloride, magnesia, magnesium carbonate, and magnesium hydrogen carbonate, with magnesia being preferred.

[0079] The content of the stabilizer source in the molded body may be the same as the stabilizer content in the desired sintered body.

[0080] When the sintered body contains alumina, the molded body may contain an alumina source. The alumina source is at least one of alumina (Al2O3) and a compound containing aluminum (Al) as a precursor thereof, and includes at least one selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide, and alumina, and is preferably alumina.

[0081] The content of the alumina source in the compact may be equal to the alumina content in the target sintered body.

[0082] To improve the shape stability, the molded body may contain a binder. The binder may be any organic binder used in molding ceramics, and may be, for example, one or more selected from the group consisting of acrylic resin, polyolefin resin, wax, and plasticizer. The binder content may be, for example, 25 to 65% by volume as the ratio of the binder to the volume of the molded body.

[0083] The shape of the molded body may be any shape depending on the purpose, taking into consideration shrinkage due to sintering, and examples thereof include at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral.

[0084] The method for producing the molded body is arbitrary, and includes mixing and molding zirconia, a stabilizer source, and, if necessary, an alumina source by any method. Also, instead of zirconia and the stabilizer source, or in addition to zirconia and the stabilizer source, stabilizer-containing zirconia may be used.

[0085] When using stabilizer-containing zirconia as the zirconia, the method of incorporating the stabilizer into the zirconia is arbitrary, for example, mixing a hydrated zirconia sol with a stabilizer source having an amount equivalent to the desired stabilizer content, followed by drying, calcining, and washing with water.

[0086] Any mixing method may be used, preferably at least one of dry mixing and wet mixing, more preferably wet mixing, and even more preferably wet mixing using a ball mill.

[0087] The molding method may be any known molding method, and is preferably at least one selected from the group consisting of uniaxial pressing, isostatic pressing, injection molding, extrusion molding, rolling granulation, and casting molding, more preferably at least one of uniaxial pressing and isostatic pressing, and even more preferably at least one of cold isostatic pressing and uniaxial pressing (powder press molding).

[0088] In the sintering process, the compact is sintered to obtain a sintered body. The sintering method is arbitrary, and may be atmospheric sintering, pressure sintering, or the like. Examples of the sintering method include known sintering methods such as sintering, vacuum sintering, etc. A preferred sintering method is atmospheric sintering, which is preferred because it is simple. This allows the sintered body of this embodiment to be obtained as a so-called atmospheric sintered body. Normal pressure sintering is a method of sintering by simply heating the compact (or calcined body) without applying an external force to it during sintering.

[0089] The conditions for the atmospheric sintering include a sintering temperature of 1250°C to 1600°C, preferably 1300°C to 1580°C, and more preferably 1300°C to 1560°C. The sintering atmosphere may be at least one of an air atmosphere and an oxygen atmosphere, and the air atmosphere is preferred. In this way, when ceria is contained as a stabilizer, the ceria is preferably tetravalent cerium (Ce 4+ ) EXAMPLES

[0090] The present embodiment will be specifically described below with reference to examples, but the present embodiment is not limited to these examples. (Confirmation of plastic deformation area) The presence or absence of plastic deformation regions in the sintered samples was confirmed by a ball drop test using a DuPont ball drop tester (H-50, manufactured by Toyo Seiki Co., Ltd.) conforming to JIS K 5600 5-3. The test conditions are as follows: Falling weight: (shape) A spherical hard ball with a diameter of 6.35 mm, i.e. a cylindrical punch with a height of 10 mm and a spherical tip with a diameter of 6.35 mm. (Mass) 300g, that is, a 300g weight made of SUS, in the shape of a rectangular parallelepiped with dimensions of 80mm width x 20mm thickness x 30mm height Drop height: 350mm Measurement sample: A sintered body in the shape of a plate with dimensions of 40 mm length x 30 mm width x 2 mm thickness, with the surface roughness of both surfaces (40 mm length x 30 mm width; main surfaces) being Ra≦0.02μm In order to prevent the sample pieces from scattering, the measurement sample was placed on the sample stage of the ball drop tester by fixing one surface of the measurement sample (a surface measuring 40 mm long x 30 mm wide) with double-sided tape. After placement, tape was applied vertically to the surface opposite the fixed surface of the measurement sample to fix the measurement sample. The hitting mold was placed so that the falling weight would fall near the center of the fixed measurement sample, and the ball drop test was performed.

[0091] (Measurement of ball drop strength) The ball drop strength was measured in the same manner as the ball drop test for confirming the plastic deformation region, except for changing the ball drop height. That is, the state of the test specimen after the drop of the weight was visually confirmed, and the ball drop strength at the ball drop height at which the test specimen was broken was calculated from the following formula. Fall strength (J) = Mass of falling weight (g) × Fall height (mm) × Gravitational acceleration (9.8 m / s 2 )

[0092] Breakage was judged to have occurred when the measurement sample was broken into two or more pieces. Note that a state in which extremely small fragments such as chipping occurred and the measurement sample maintained its plate-like shape was not considered to have broken. If no breakage occurred in the ball drop test at a specific drop height, the ball drop test was repeated by increasing the drop height in 50 mm increments up to 500 mm until breakage occurred. For measurement samples that did not break in the 500 mm drop test, the ball drop strength was conveniently determined to be > 5J (more than 5J). (Impact mark depth) The depth of the impact mark was measured at a magnification of 20x using a general laser microscope (device name: VK-9500 / VK-9510, manufactured by Keyence Corporation). A line profile was made passing through the center of the impact mark, and the length (L1) of the deepest part was measured in the Z-axis direction at 0.5 μm / step. Then, a line profile was made in the same manner so as to be perpendicular to the line profile, and the length (L2) of the deepest part was measured in the Z-axis direction. The lengths of both the deepest parts obtained were averaged (=(L1+L2) / 2), and the obtained length was determined as the depth of the impact mark. (Vickers hardness) The Vickers hardness was measured using a common Vickers tester (device name: MV-1, manufactured by Matsuzawa Co., Ltd.) equipped with a square pyramid indenter made of diamond.

[0093] The indenter was statically pressed into the surface of the test sample, and the diagonal length of the indentation formed on the surface of the test sample was visually measured. The obtained diagonal length was used to calculate the Vickers hardness (GPa) according to the above formula. (density) The measured density of a sintered sample is the ratio of the volume measured by Archimedes' method to the mass measured by mass measurement (g / cm 3 ) was calculated. (I (004) / (220) ) Crystal phase of sintered sample, T 004 and T 220 The diffraction intensity was measured using a micro-XRD (device name: X'pert PRO MPD, manufactured by Spectris Corp.) The measurement conditions are as follows. Radiation source: CuKα radiation (λ=1.5405Å) Tube voltage: 45kV Tube current: 40mA High-speed detector: X'Celerator + Ni filter Micro optical system: Monocapillary, diameter 0.1 mm Measurement angle: 70~80° Goniometer: Radius 240mm

[0094] Before the test and after the confirmation of the plastic deformation region, micro-area XRD measurements were performed on the impact core and areas other than the impact core of the measurement sample. (004) / (220) was calculated according to the following formula: I (004) / (220) =(T 004 Diffraction intensity of 220 Diffraction strength of degrees)

[0095] (Color Tone Measurement) The color tone of the sintered samples was measured according to the method of JIS Z8722. A spectrophotometer (device name: CM-700d, manufactured by Konica Minolta) was used, and measurements were made against a black background using a black board on the back. The measurement conditions were as follows. Light source: F2 light source Viewing angle: 10° Measurement method: SCI

[0096] The sintered body sample used was a disk-shaped sample with a diameter of 20 mm and a thickness of 2.7 mm. One surface of the sintered body sample was mirror-polished (Ra≦0.02 μm), and the color tone was evaluated using this surface as the evaluation surface. The effective area for color tone evaluation was 10 mm in diameter.

[0097] Example 1 A hydrated zirconia sol was obtained by hydrolysis of an aqueous solution of zirconium oxychloride. Yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 1.1 mol% and the ceria concentration was 3.4 mol%. After mixing, the mixture was dried in the air and calcined at 1155°C in the air for 2 hours to obtain calcined yttria-ceria stabilized zirconia powder. The calcined powder obtained was washed with pure water and dried to obtain zirconia powder consisting of yttria and ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.4 mol%.

[0098] The obtained powder and α-alumina powder with an alumina content of 5 mass% were added to pure water to form a slurry, which was then ground and mixed for 18 hours in a ball mill using zirconia balls with a diameter of 10 mm as a grinding medium. The slurry after grinding and mixing was dried to obtain the zirconia powder of this example, which contains 5 mass% alumina and the remainder is yttria- and ceria-stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.4 mol%.

[0099] The obtained powder was granulated to obtain powder granules, which were then packed into a plate-shaped mold measuring 40 mm in length and 30 mm in width, and subjected to uniaxial pressing at a molding pressure of 50 MPa and cold isostatic pressing (CIP) at a molding pressure of 196 MPa to obtain a plate-shaped green body (green compact). The obtained green body was sintered under the following conditions to obtain a sintered body of this example consisting of yttria-ceria stabilized zirconia containing 5 mass% alumina with the remainder containing 1.1 mol% yttria and 3.4 mol% ceria. The sintering conditions are shown below. Sintering method: Pressureless sintering Sintering atmosphere: Air Sintering temperature: 1550℃ Sintering time: 2 hours

[0100] Example 2 The zirconia powder of this example was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added to and mixed with the hydrated zirconia sol so that the ceria concentration was 3.9 mol %. The powder contained 5 mass % alumina, with the remainder being yttria-ceria stabilized zirconia with an yttria content of 1.1 mol % and ceria content of 3.9 mol %.

[0101] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, which was made of yttria-ceria stabilized zirconia containing 5 mass% alumina and the remainder containing 1.1 mol% yttria and 3.9 mol% ceria.

[0102] Example 3 The zirconia powder of this example was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added to and mixed with the hydrated zirconia sol so that the ceria concentration was 5.0 mol %, and the remainder was yttria-ceria stabilized zirconia with an yttria content of 1.1 mol % and a ceria content of 5.0 mol %.

[0103] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, which consisted of yttria-ceria stabilized zirconia containing 5 mass% alumina, with the remainder being 1.1 mol% yttria and 5.0 mol% ceria.

[0104] Example 4 The zirconia powder of this example was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 0.7 mol% and the ceria concentration was 5.0 mol%, respectively. The powder contained 5 mass% alumina, with the remainder being yttria-ceria stabilized zirconia with a content of 0.7 mol% yttria and 5.0 mol% ceria.

[0105] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 5 mass% alumina, with the remainder being 0.7 mol% yttria and 5.0 mol% ceria.

[0106] Example 5 The zirconia powder of this example was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 1.0 mol% and the ceria concentration was 3.6 mol%, respectively. The powder contained 5 mass% alumina, with the remainder being yttria-ceria stabilized zirconia with an yttria content of 1.0 mol% and an ceria content of 3.6 mol%.

[0107] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, which consisted of yttria-ceria stabilized zirconia containing 5 mass% alumina, with the remainder being 1.0 mol% yttria and 3.6 mol% ceria.

[0108] Comparative Example 1 The zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that yttria was added and mixed with the hydrated zirconia sol so that the yttria concentration was 1.5 mol %. The zirconia powder contained 5 mass % alumina, with the remainder being yttria content of 1.5 mol % and ceria content of 3.4 mol %, and was made of yttria-ceria stabilized zirconia.

[0109] A sintered body for this comparative example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 5 mass% alumina with the remainder being 1.5 mol% yttria and 3.4 mol% ceria.

[0110] Comparative Example 2 The zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 2.0 mol% and the ceria concentration was 3.9 mol%, respectively. The powder contained 5 mass% alumina, with the remainder being yttria-ceria stabilized zirconia with an yttria content of 2.0 mol% and ceria content of 3.9 mol%.

[0111] A sintered body for this comparative example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 5 mass% alumina, with the remainder being 2.0 mol% yttria and 3.9 mol% ceria.

[0112] Comparative Example 3 The zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 3.0 mol% and the ceria concentration was 3.9 mol%, respectively. The powder contained 5 mass% alumina, with the remainder being yttria content of 3.0 mol% and ceria content of 3.9 mol%, and was composed of yttria-ceria stabilized zirconia.

[0113] A sintered body for this comparative example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 5 mass% alumina, with the remainder being 3.0 mol% yttria and 3.9 mol% ceria.

[0114] Comparative Example 4 A zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that yttria was not added to the hydrated zirconia sol, the zirconia powder being made of ceria-stabilized zirconia containing 5 mass% alumina and the remainder containing 3.4 mol% ceria.

[0115] A sintered body of this comparative example was obtained, which was made of ceria-stabilized zirconia containing 5 mass % alumina and the remainder containing 3.9 mol % ceria, in the same manner as in Example 1, except that the obtained zirconia powder was used.

[0116] Comparative Example 5 A zirconia powder of this comparative example, made of yttria-stabilized zirconia with an yttria content of 3.0 mol%, was obtained in the same manner as in Example 1, except that yttria was added and mixed with the hydrated zirconia sol so that the yttria concentration was 3.0 mol%, and that cerium chloride heptahydrate and α-alumina powder were not used.

[0117] A sintered body of this comparative example made of yttria-stabilized zirconia with an yttria content of 3.0 mol% was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used and the sintering temperature was set to 1500°C.

[0118] The results of the above examples and comparative examples are shown in the table below.

[0119] [Table 1]

[0120] In the above table, the column "Formation of Impact Mark" indicates that the impact mark was confirmed after the ball drop test, and the column "x" indicates that the impact mark was not confirmed. FIG. 7 shows the appearance of the sintered body after the ball drop test of Example 1. From FIG. 7, it can be seen that the area where the falling weight contacted in the ball drop test formed an impact mark (concave) without any destruction such as cracks, that is, the impact mark (concave) as a trace of plastic deformation. FIG. 8 shows the appearance of the impact mark enlarged by optical microscope observation (magnification: 20 times). The impact mark was a round concave with a diameter of about 2.8 mm, and the depth of the impact mark (concave) relative to the thickness of the sintered body was 2.5. Moreover, Examples 1 to 5, in which the yttria content was 0.7 mol% or more and less than 1.5 mol%, were all sintered bodies with a zirconia content of 95 mass% and a tetragonal crystal phase, and had a density equivalent to a relative density of 98% or more. Impact marks as traces of plastic deformation could be visually confirmed in these sintered bodies, similar to those in Fig. 7. In Examples 1 to 5, no effect of the ceria content on the formation of impact marks was observed, but it was confirmed that all of the sintered bodies in these Examples had a ball drop strength of 1 J or more, regardless of the ceria content.

[0121] FIG. 9 shows the appearance of the sintered body of Comparative Example 3 after the ball drop test, as observed under an optical microscope (magnification: 20 times). In Comparative Example 3, it can be observed that no impact mark due to plastic deformation is formed, and cracks due to Hertzian fracture develop, causing the sintered body to break. On the other hand, in the sintered body with an yttria content of 1.5 mol% or more, no impact mark can be confirmed, and the ball drop strength is 0.4 J or less, which indicates that the impact resistance is extremely low. In Comparative Example 4, which does not contain yttria, defects such as cracks are generated during sintering, and a measurable sintered body could not be obtained. Furthermore, it was confirmed from Comparative Example 5 that the sintered body containing only yttria as the stabilizer does not have a plastic deformation region.

[0122] The sintered body of Example 1 had a surface I (004) / (220) And other than the core part I (004) / (220) The I value of the impact point after the ball drop test was 0.55. (004) / (220)The value was 3.43. This shows that the ball drop test caused regions with different crystal orientations to appear in the sintered body.

[0123] The sintered bodies of Examples 1 to 6 all have the same color tone. For example, the sintered body of Example 1 has a color tone of L * = 92.41, a * =-3.89 and b * = 16.01, and the sintered body of Example 4 is L * = 93.21, a * =-3.18 and b * =18.38.

[0124] Example 6 The zirconia powder of this example, consisting of yttria-ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.9 mol%, was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added to and mixed with the hydrated zirconia sol so that the ceria concentration was 3.9 mol%, and that a slurry was prepared instead of using α-alumina powder.

[0125] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, and the remainder was yttria-ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.9 mol%.

[0126] Example 7 The zirconia powder of this example was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added and mixed with the hydrated zirconia sol so that the ceria concentration was 3.9 mol%, and α-alumina powder was added to form a slurry so that the alumina content was 1 mass%. The remainder was yttria-ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.9 mol%.

[0127] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 1 mass% alumina, with the remainder being 1.1 mol% yttria and 3.9 mol% ceria.

[0128] Example 8 The zirconia powder of this example was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added and mixed with the hydrated zirconia sol so that the ceria concentration was 3.9 mol%, and α-alumina powder was added to form a slurry so that the alumina content was 3 mass%. The remainder was yttria-ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.9 mol%.

[0129] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, which was made of yttria-ceria stabilized zirconia containing 3 mass% alumina and the remainder containing 1.1 mol% yttria and 3.9 mol% ceria.

[0130] Example 9 The zirconia powder of this example was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added to and mixed with the hydrated zirconia sol so that the ceria concentration was 3.9 mol%, and α-alumina powder was added to form a slurry so that the alumina content was 7 mass%. The remainder was yttria-ceria stabilized zirconia with an yttria content of 1.1 mol% and a ceria content of 3.9 mol%.

[0131] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 7 mass% alumina, with the remainder being 1.1 mol% yttria and 3.9 mol% ceria.

[0132] Example 10 The zirconia powder of this example was obtained in the same manner as in Example 1, except that α-alumina powder was added to prepare a slurry so that the alumina content was 10 mass%. The slurry was made of yttria-ceria stabilized zirconia containing 10 mass% alumina, with the remainder containing 1.1 mol% yttria and 3.4 mol% ceria.

[0133] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, which was made of yttria-ceria stabilized zirconia containing 10 mass% alumina, with the remainder being 1.1 mol% yttria and 3.4 mol% ceria.

[0134] Example 11 α-alumina powder was added to the slurry so that the alumina content was 16.4 mass%. The zirconia powder of this example was obtained in the same manner as in Example 1, except that the alumina powder was changed to yttria-ceria stabilized zirconia containing 16.4 mass% alumina, with the remainder being 1.1 mol% yttria and 3.4 mol% ceria.

[0135] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used. The sintered body was made of yttria-ceria stabilized zirconia containing 16.4 mass% alumina, with the remainder being 1.1 mol% yttria and 3.4 mol% ceria.

[0136] The results of the above examples are shown in the table below.

[0137] [Table 2]

[0138] From the above table, it can be confirmed that the sintered bodies of these Examples have a relative density equivalent to 98% or more, and that impact marks are formed regardless of the presence or absence of alumina content and its content. Furthermore, it can be confirmed that a plastic deformation region is present when the zirconia content is in the range of 83.6 mass% or more and 100 mass% or less. Note that the depth of the impact core portion relative to the thickness of the sintered body of the sintered body of Example 6 was 2.6. It can also be confirmed that the Vickers hardness tends to increase with increasing alumina content.

[0139] The sintered bodies of Examples 6 to 11 all had the same color tone. For example, the sintered body of Example 6 had a color tone of L * = 83.98, a * =-4.69 and b * = 20.00, and the sintered body of Example 9 is L * = 94.38, a * =-3.64 and b * = 14.13, and the sintered body of Example 10 has L * = 95.26, a * =-3.45 and b * =14.22.

[0140] Example 12 The sintered body of this example was obtained in the same manner as in Example 6, except that the sintering temperature was 1450°C.

[0141] Example 13 The sintered body of this example was obtained in the same manner as in Example 7, except that the sintering temperature was 1450°C.

[0142] Example 14 The sintered body of this example was obtained in the same manner as in Example 8, except that the sintering temperature was 1450°C.

[0143] Example 15 The sintered body of this example was obtained in the same manner as in Example 2, except that the sintering temperature was 1450°C.

[0144] Example 16 The sintered body of this example was obtained in the same manner as in Example 9, except that the sintering temperature was 1450°C.

[0145] The results of the above examples are shown in the table below.

[0146] [Table 3]

[0147] From Table 2 and the table above, it can be seen that even pressureless sintered bodies obtained at higher sintering temperatures have a relative density equivalent to 98% or more, have a plastic deformation region, and tend to have higher hardness and lower ball drop strength as the sintering temperature decreases.

[0148] The sintered bodies of Examples 12 to 16 all had the same color tone. For example, the sintered body of Example 12 had a color tone of L * = 83.52, a * =-4.75 and b * = 24.35, and the sintered body of Example 15 is L * = 94.18, a * =-3.93 and b * =16.79.

[0149] Example 17 The zirconia powder of this example, consisting of yttria-ceria stabilized zirconia with an yttria content of 1.2 mol% and a ceria content of 3.6 mol%, was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 1.2 mol% and the ceria concentration was 3.6 mol%, respectively, and that no α-alumina powder was used.

[0150] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, and the remainder was yttria-ceria stabilized zirconia with an yttria content of 1.2 mol% and a ceria content of 3.6 mol%.

[0151] Example 18 The zirconia powder of this example, consisting of yttria-ceria stabilized zirconia with an yttria content of 1.0 mol% and a ceria content of 4.0 mol%, was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 1.0 mol% and the ceria concentration was 4.0 mol%, respectively, and that no α-alumina powder was used.

[0152] A sintered body of this example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, and the remainder was yttria-ceria stabilized zirconia with an yttria content of 1.0 mol% and a ceria content of 4.0 mol%.

[0153] Comparative Example 6 The zirconia powder of this comparative example, consisting of yttria-ceria stabilized zirconia with an yttria content of 3.0 mol% and a ceria content of 3.9 mol%, was obtained in the same manner as in Example 1, except that yttria and cerium chloride heptahydrate were added to and mixed with the hydrated zirconia sol so that the yttria concentration was 3.0 mol% and the ceria concentration was 3.9 mol%, respectively, and that no α-alumina powder was used.

[0154] A sintered body for this comparative example was obtained in the same manner as in Example 1, except that the obtained zirconia powder was used, with the remainder being yttria-ceria stabilized zirconia with an yttria content of 3.0 mol% and ceria content of 3.9 mol%.

[0155] The results of the examples and comparative examples are shown in the table below.

[0156] [Table 4]

[0157] From Examples 17 and 18, and from Example 12, it can be confirmed that even the sintered body made of yttria and ceria-stabilized zirconia without containing alumina has a plastic deformation region. On the other hand, the sintered body of Comparative Example 6, although the ceria content is less than that of Example 18, does not have a plastic deformation region and the I of the surface before the drop test is small. (004) / (220) And other than the core part I (004) / (220) is 0.38, and the I (004) / (220) is 0.80, and the I (004) / (220) No significant changes were observed. [Explanation of symbols]

[0158] 100: Overview of the drop ball test 101: Sintered body 102: Punch 103a, 103b: Guide 104: Falling weight 105: Fixing tape 106: Sample stand for the ball drop test machine 107: Protective tape 200: Sintered body of this embodiment after drop test 201: Sintered body 202: Impact mark (dent) 203: Depth of impact mark (dent) 300: Conventional sintered body after drop test 301: Sintered body 302: Defect (crack) 400: A diagram showing the state of a sintered body placed on the sample stage of a drop test machine. 401: Sintered body 402: Fixing tape 403: Sample stand for the ball drop test machine 404: Double-sided tape (protective tape) 500: Diagram showing how to measure impact mark depth 501: Sintered body 502: Impact mark (dent) 503A,B: Line profile 504: Depth of deepest part (L1 or L2) 601: Sintered body in a divided state 602: Defect (crack) 702: Impact mark (dent)

Claims

1. A sintered body comprising zirconia containing a stabilizer, and characterized in that when an impact force is applied, the sintered body has a region in which the intensity of the powder X-ray diffraction peak of the tetragonal (004) plane is greater than 1.0 and is not greater than 10 relative to the intensity of the powder X-ray diffraction peak of the tetragonal (220) plane.

2. The sintered body according to claim 1 , wherein the impact mark is a recess.

3. 3. The sintered body according to claim 1, wherein the stabilizer content is from 3 mol % to 10 mol %.

4. 4. The sintered body according to claim 1, wherein the stabilizer is two or more selected from the group consisting of yttria, calcia, magnesia and ceria.

5. 5. The sintered body according to claim 1, wherein the stabilizer is yttria and ceria.

6. 6. The sintered body according to claim 1, wherein the yttria content is less than 1.5 mol%.

7. The sintered body according to claim 1 , having a ceria content of 2 mol % or more and 7.5 mol % or less.

8. The sintered body according to claim 1 , comprising alumina.

9. 9. The sintered body according to claim 5, wherein a ratio (molar ratio) of the stabilizing element other than yttrium to yttrium is 1.2 or more and 5.0 or less.

10. CIE1976(L * a * b * ) Lightness in color space L * The sintered body according to claim 1 , wherein the Mn content is 80 or more.

11. 9. The sintered body according to claim 1, having a Vickers hardness of 12 GPa or less.

12. A member comprising the sintered body according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • High tenacity zirconia sintered body

    JP1986077665A

  • Heat-resistant water-stable and high-toughness zirconia sintered body

    JP1986219756A

  • Zirconia ceramics

    JP1988139049A

  • Zirconia-alumina composite ceramic material

    JP2005097094A

  • Sintered formed body and method of manufacturing the same and application of the same

    JP2008037746A